2021
DOI: 10.1016/j.chembiol.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of kinase polypharmacology across HSP90 drug discovery

Abstract: Highlights d Characterization of kinase polypharmacology landscape for HSP90 inhibitors d Ganetespib and luminespib display unique polypharmacology d Kinase polypharmacology evolved during optimization to discover luminespib d Earlier characterization of polypharmacology in drug discovery is recommended

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…It is noted that Antolin et al. recently revealed several kinases as potential off‐targets of Luminespib, [25] demonstrating the significance of unique kinase polypharmacology in developing Hsp90 inhibitors . On the other hand, kinases were not prominently enriched in our chemoproteomic experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that Antolin et al. recently revealed several kinases as potential off‐targets of Luminespib, [25] demonstrating the significance of unique kinase polypharmacology in developing Hsp90 inhibitors . On the other hand, kinases were not prominently enriched in our chemoproteomic experiments.…”
Section: Resultsmentioning
confidence: 99%
“…[23] Interestingly, PTGES2, an isomerase involved in prostaglandin E2 metabolism, was recently developed as a promising therapeutic target for COVID-19 treatment. [24] It is noted that Antolin et al recently revealed several kinases as potential off-targets of Luminespib, [25] demonstrating the significance of unique kinase polypharmacology in developing Hsp90 inhibitors . On the other hand, kinases were not prominently enriched in our chemoproteomic experiments.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study evaluated the kinase inhibition of these heat shock protein HSP90 inhibitors. [149] Experimental screening of their inhibitory potency against a kinase panel revealed distinct coverage of the orthosteric ATPsite binders, with ganetespib and luminespib respectively inhibiting 21 and 2 out of 382 kinases, and a retrospective analysis showed that the kinase polypharmacology of luminespib markedly evolved during the hit-to-lead drug discovery process. Combinations of HSP90 and kinase inhibitors are potential cancer treatment, and kinases lend themselves to ABPP due to the availability of potent, cell-permeable probes, which could facilitate repurposing strategies.…”
Section: New Trends In Drug Discoverymentioning
confidence: 99%
“…Ganetespib and luminespib are drug candidates for the treatment of cancer. A recent study evaluated the kinase inhibition of these heat shock protein HSP90 inhibitors [149] . Experimental screening of their inhibitory potency against a kinase panel revealed distinct coverage of the orthosteric ATP‐site binders, with ganetespib and luminespib respectively inhibiting 21 and 2 out of 382 kinases, and a retrospective analysis showed that the kinase polypharmacology of luminespib markedly evolved during the hit‐to‐lead drug discovery process.…”
Section: New Trends In Drug Discoverymentioning
confidence: 99%
“…Inhibition of the catalytic phosphate transfer activity, which is essential for many signal transduction events, is by far the most widely applied strategy for therapeutic intervention of abnormal kinase functions. , Protein kinase inhibitors (PKIs) are used in a variety of therapeutic areas. The first PKIs marketed as drugs were developed for cancer treatment, and their therapeutic effects largely depended on multi-kinase engagement and the resulting polypharmacology. ,,, In other therapeutics areas such as inflammatory or metabolic diseases, kinase-selective inhibitors are preferentially used, especially for the treatment of chronic medical conditions. ,,, PKIs are distinguished by different mechanisms of actions. , Most kinase inhibitors bind to the adenosine triphosphate (ATP) cofactor binding site or proximal to this site (type I, I1/2, and II inhibitors) and compete with ATP binding. Since the ATP binding site is mostly conserved across the human kinome, these inhibitors are expected to have multi-kinase activity.…”
Section: Introductionmentioning
confidence: 99%